Pendekatan Multisensori dalam Desain Media Pembelajaran Augmentasi bagi Anak dengan Disleksia - Fonita Theresia Yoliando (ULTIMART Jurnal Komunikasi Visual, 2022)
The human brain is a complex structure that allows us to encode and decode various stimuli that incorporate the five senses. In the case of children with dyslexia, this information processing performs inefficiently which resulted in reading, spelling, and/ or writing difficulties. Other related difficulties, such as memorizing, organizing, sequencing, and motor skills deficiency, may also be present. This specific learning difference is a lifetime challenge that cannot be cured, but it can be overcome through structured interventions. For many years, the multi-sensory approach utilized visual, auditory, and kinesthetic-tactile to trigger the senses, which is well known as one of the most compelling aspects of instruction for dyslexic students. By simultaneously training the brain through the senses, it is hypothesized that this approach can enhance the phonetical ability in a more effective and meaningful way through the implementation of an interactive learning kit for dyslexia. This paper is an initial phase of long-term research about an interactive learning kit for dyslexia. It includes the analysis of a multi-sensory approach and how it can be implemented in the design and development process in the next phase. Keywords: dyslexia; multi-sensory; interactive; learning.